Efficiency and Ownership Structure: The Case of Poland - Karl-Markus Modén; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2007)
We examine the effects of foreign entry on productive efficiency during the Polish investment liberalization. The performance of foreign acquisitions is compared to foreign firms entering the market through greenfield entry, as well as domestic acquisitions of privatized firms, domestic greenfields and remaining state-owned (non-privatized) firms during the period 1995-2000. We find that foreign privatized firms have realized larger productivity gains than all types of domestic firms and that this is not due to higher price-cost margins, which is consistent with the idea that foreign firms bring in firm-specific knowledge. Foreign greenfields have the highest average labour productivity, while foreign privatizations show the largest productivity increase.
Keywords: F23; J31; 330; Privatizations; M As; FDI; Foreign Ownership; Productivity; Direktinvestition; Privatisierung; Übernahme; Produktivität; Polen